Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1037/emo0000714
|View full text |Cite
|
Sign up to set email alerts
|

Incidental fear reduces empathy for an out-group’s pain.

Abstract: Humans generally fear those different to them (i.e. an out-group) in the same way they fear natural predators. But fear pushes us to derogate others, whether they constitute a threat or not. Research has examined how fear associated with specific intergroup relations interferes with how individuals relate to in-group and out-group members. However, we know relatively little about how intergroup relations might be affected by incidental emotions. We tested how incidental fear affects empathy towards in-group an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“…Concomitantly, empathy constructs did not play a predictive role in the stigma factors of the dangerousness model in the present study. This is in line with previous studies which specified that one of the main factors influencing empathy and its role in promoting prosocial behaviors is the perception of other people as threatening (Richins et al, 2021). When an individual is confronted to an impending or perceived threat, emotion of fear will be triggered and motivate self-protecting reactions (i.e., fight or flight response; Nabi, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Concomitantly, empathy constructs did not play a predictive role in the stigma factors of the dangerousness model in the present study. This is in line with previous studies which specified that one of the main factors influencing empathy and its role in promoting prosocial behaviors is the perception of other people as threatening (Richins et al, 2021). When an individual is confronted to an impending or perceived threat, emotion of fear will be triggered and motivate self-protecting reactions (i.e., fight or flight response; Nabi, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Literature in psychosocial sciences has shown that stress [9] , fear [10] , or emergency [11] influence human relationships; research shows that the sense of belonging to the group and the contact with others’ emotions [12] play a central role in reducing these risks [13] . Studies suggest that workplaces aiming to increase job satisfaction can do so, through well-organized gratitude interventions [14] .…”
mentioning
confidence: 99%
“…Along with other conditions such as stress and competition, fear tends to diminish empathy (Crawford 2014). Even incidental fear (random fearful imaginary) negatively affects empathy toward out-group suffering (Richins et al 2019). Explicit competition among groups (about, for example, access to jobs or healthcare) can even create counter-empathic reactions.…”
Section: Analyzing Emotions In Crisis Situations: Framing and Emotion-based Strategiesmentioning
confidence: 99%